Sistem Pendukung Keputusan Pemilihan Laptop Untuk Kebutuhan Pemrograman Mahasiswa Teknik Informatika Menggunakan Metode COPRAS - Naufal Altaris Aryadhana; Bagas Andrean; Zaki Alwiansyah; Yuyun Dwi Lestari (STKIP Subang, 2026)
Selecting a suitable laptop for programming needs is important for informatics students to support their studies and software development. The large number of laptop options with varying specifications and prices often causes students to have difficulty in determining the laptop that best suits their needs. Therefore, a Decision Support System (DSS) is needed that can assist the laptop selection process objectively. This study aims to build a Decision Support System for selecting a laptop for the programming needs of informatics students using the Complex Proportional Assessment (COPRAS) method. This study uses secondary data obtained from the official websites and online catalogs of laptop manufacturers. The COPRAS method is used to evaluate and rank three alternative laptops, namely Lenovo IdeaPad Slim 3, Acer Aspire 5, and HP Pavilion 14, based on four main criteria: price, RAM capacity, SSD capacity, and battery life. The calculation results show that the Acer Aspire 5 obtained the highest relative weight value (Qi) of 0.3534 with a performance index (Pi) of 100%, thus ranking first. The second rank was obtained by the HP Pavilion 14 with a Qi of 0.3491 and a Pi of 98.76%. The third rank was obtained by the Lenovo IdeaPad Slim 3 with a Qi of 0.2975 and a Pi of 84.17%. The COPRAS method is proven to be able to produce objective, consistent, and quantitatively measurable laptop recommendations based on the criteria of price, RAM, SSD capacity, and battery life, thereby helping informatics students determine the most suitable laptop for programming needs.